Procurement Planning and Procurement Performance for Operations and Projects in Public Sector Entities - A Case of Uganda Management Institute - Alex Nduhura; Innocent Nuwagaba; Thekiso molokwane; MT Tshombe Lukamba (International Journal of Supply Chain Management, 2021)
The study investigated the influence of procurement planning on procurement performance in Public Higher Education Institutions by focusing on UMI. The study was guided by the resource-based view (RBV) theory and the European foundation for quality management model. In Uganda most government Institutions such as UMI have registered certain constraints in procurement performance and this could be a result of inadequate procurement planning on a timely basis as required by the PPDA Act 2003. The objectives of the study were: to find out the relationship between procurement needs assessment and procurement performance, to examine the relationship between procurement budgeting and procurement performance and to analyze the relationship between information sharing and procurement performance at UMI. The study used the cross sectional research design. The sample size comprised of 119 stakeholders and the response rate was 63%. The information got from the data collection instrument was analyzed by the researcher and the findings of the study were: there is a strong positive relationship between needs assessment and procurement performance, there is a weak positive relationship between procurement budgeting and procurement performance and there is a fairly positive relationship between information sharing and procurement performance. It was concluded that there is a close relationship between Procurement planning and organizational performance of operations and projects of public Higher Education Institutions in Uganda. It was recommended that the PDU should always liaise with User Departments to ensure that they undertake a thorough needs assessment, the heads of departments should always ensure that they involve their subordinates in procurement budgeting and that the PDU should always avail the User Departments, with the right PPDA procedures and guidelines on procurement planning and budgeting.